Efforts to Increase the Fisherman Income Through Financial Management of the Independent Fisherman Group in Village Mattiro Bombang, Pangkep Regency - Junaedi, Junaedi; Handam, Handam (Journal La Bisecoman, 2020)
This article aims to provide a practical picture to strengthen understanding of the concept of investment plans and the process of preparing a follow-up plan for the design of a village investment committee design and enhancing the knowledge and skills of participants in implementing financial management at the scale of fishermen groups. The method to be used in this training is a participatory method, considering that this method is the most relevant for adult learning methods (andragogy) and the most suitable also for discussing community empowerment programs in development. Training with participatory methods is characterized by respect for the participants. Through training on the financial management of fishermen groups, it is hoped that they can provide understanding to village officials in knowing and carrying out management of fishermen groups. The results of the activity showed the enthusiasm of the participants in the lecture material and discussion session because their views which had been difficult to keep in bookkeeping and governance could be delivered simply and applicatively to the fishing community level. This strategy is to anticipate the fulfillment of the necessities of life, among others by saving and investing, forming a social gathering group, borrowing money, and migrating to other places outside the waters around where they live.